The Role of Intestinal Mucosal Barrier in Autoimmune Disease: A Potential Target - An, Jia; Liu, Yuqing; Wang, Yiqi; Fan, Ru; Hu, Xiaorong; Zhang, Fen; Yang, Jinhua; Chen, Junwei (Frontiers in Immunology, 2022)
Autoimmune diseases are a series of diseases involving multiple tissues and organs characterized with impaired immune balance leading to the production of abnormal multiple antibodies. The pathogenesis of it is not yet fully understood. Intestinal immunity, especially the intestinal mucosal barrier has become a research hotspot. And current research supports that intestinal mucosal barrier is an upstream mechanism leading to impaired immune balance and is considered to be an important role in participating in the pathogenesis of autoimmune diseases. As an important defense barrier, intestinal mucosal barrier regulates homeostasis and maintains the stability of internal environment through physical, chemical, immune and biological barriers. Once the intestinal barrier function is impaired under the effect of multiple factors, it will destroy immune homeostasis, trigger inflammatory reactions, and participate in the development of autoimmune diseases in the final. However, the mechanism of intestinal mucosal barrier regulating the homeostasis and inflammation of body is not clear, and some studies suggest that it maintains the balance of immune homeostasis through the zonulin pathway, intestinal microbiome and Toll-like receptor signaling pathway. This review focuses on the role of intestinal mucosal barrier in the development of autoimmune diseases, aiming to explore its potential therapeutic targets in autoimmune diseases by introducing the composition and function of intestinal mucosal barrier and describing its research progress in regulating immune homeostasis and inflammation.